1989
DOI: 10.1021/bi00445a045
|View full text |Cite
|
Sign up to set email alerts
|

RNA chain initiation by Escherichia coli RNA polymerase. Structural transitions of the enzyme in early ternary complexes

Abstract: We have studied the properties and structures of a series of Escherichia coli RNA polymerase ternary complexes formed during the initial steps of RNA chain initiation and elongation. Five different templates were used that contained the bacteriophage T7 A1 promoter or the E. coli Tac or the lac UV5 promoter, as well as variant templates with alterations in the initial transcribed regions. The majority of ternary complexes bearing short transcripts (from two to nine nucleotides) are highly unstable and cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
183
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(193 citation statements)
references
References 46 publications
9
183
1
Order By: Relevance
“…For many years, it was widely believed that the transition to transcription elongation caused all 70 to be released from RNAP. A number of biochemical studies showed that ␤ and 70 could be purified from initiating but not from elongating RNAP complexes (2)(3)(4)(5). These data are consistent with structural studies of RNAP that suggest would be displaced from RNAP holoenzyme by RNA products of 12-14 nt in length (6).…”
supporting
confidence: 74%
“…For many years, it was widely believed that the transition to transcription elongation caused all 70 to be released from RNAP. A number of biochemical studies showed that ␤ and 70 could be purified from initiating but not from elongating RNAP complexes (2)(3)(4)(5). These data are consistent with structural studies of RNAP that suggest would be displaced from RNAP holoenzyme by RNA products of 12-14 nt in length (6).…”
supporting
confidence: 74%
“…Such a model is not easily reconciled with bulk footprinting data which suggest that the abortive initiation process results from an inability of RNAP to break its promoter contacts (54)(55)(56). These observations led Straney and Crothers to propose that the energy required to break free of the promoter might be somehow stored in a "stressed intermediate," and that abortive initiation was a consequence of this energy not being used productively (55).…”
Section: Abortive Initiationmentioning
confidence: 79%
“…In general, transcription complexes stalled near the promoter (within the first 8 -10 bases) are much less stable than those stalled very distant from the promoter (1)(2)(3)(4). The transition between initiation and elongation is a complex process, involving release of stable promoter contacts and rearrangement of the protein and the nucleic acid (5-7).…”
mentioning
confidence: 99%